Extensive stability assessment of TiO2/polyvinyl ether nanolubricant with physical homogenization - Mohd Farid, Ismail; Wan Hamzah, Azmi; Rizalman, Mamat; Sharma, Korada Viswanatha; Hafiz, Muhammad Ali (MDPI, 2023)
Proper preparation and stability evaluation of the nanolubricant shall be established when applying the nanoparticle dispersion technique in a two-phase system. The stability of the nanolubricant ensures the maximum benefit gained from the dispersion of nanoparticles in specified Polyvinyl ether (PVE). In this study, TiO2/PVE nanolubricant was prepared using two methods of physical homogenization: high-speed homogenizer (HSH) and ultrasonication bath. The HSH used a preparation time of up to 300 s in the stability assessment. Meanwhile, the ultrasonication bath had a preparation time of 1, 3, 5, and 7 h. The stability condition of the nanolubricant was evaluated using photo capturing, ultraviolet-visible (UV-Vis) spectrophotometer, zeta potential, and zeta sizer. A sample with 180 s of preparation time shows the best stability condition from HSH. The nanolubricant with ultrasonication offers excellent stability at 5 h of homogenizing time with a concentration ratio of more than 90% for up to 30 days of observation. In conclusion, ultrasonication homogenizing methods show better results than HSH with a zeta potential of more than 60 mV. In addition, HSH can be recommended as an optional method to produce nanolubricant with a low preparation time for immediate use.